2002
DOI: 10.1111/j.1745-7599.2002.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnet Therapy: What's the Attraction?

Abstract: Credibility for advanced practice will be established across disciplines as nurses demonstrate their ability to critically evaluate practices. Alternative therapies are accepted and used by many patients today. While magnet therapy is popular, the scientific evidence to support its use is limited, at best. Advanced practice nurses have more effective treatment modalities in their repertoire and are advised to avoid practices for which efficacy is unsupported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…These mechanisms may alter the firing rate of neurons, change the rate of enzyme-mediated reactions, affect calcium channels, or increase local blood circulation 12,13 . However, the supporting evidence for any of these effects is not strong 4 and the issue of effect mechanism remains vexatious. Information regarding possible mechanisms of effect would assist in defining the specific conditions for which static magnetic field therapy may have benefit, optimize its application and thus promote improved research.…”
Section: Physiological Effects Of Static Magnetsmentioning
confidence: 99%
See 2 more Smart Citations
“…These mechanisms may alter the firing rate of neurons, change the rate of enzyme-mediated reactions, affect calcium channels, or increase local blood circulation 12,13 . However, the supporting evidence for any of these effects is not strong 4 and the issue of effect mechanism remains vexatious. Information regarding possible mechanisms of effect would assist in defining the specific conditions for which static magnetic field therapy may have benefit, optimize its application and thus promote improved research.…”
Section: Physiological Effects Of Static Magnetsmentioning
confidence: 99%
“…Ratterman et al 4 carried out a review of scientific peerreviewed publications regarding magnetic therapy and found that while magnetic therapy was gaining popularity, the scientific evidence to support its efficacy in pain management was lacking. A more recent systematic review by Pittler, Brown and Ernst 22 concluded that the available evidence does not support the use of static magnets for pain relief.…”
Section: Magnet Therapy and Neuromusculoskeletal Pain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In several small clinical studies, researchers report SMF therapeutic benefit for conditions such as: diabetic peripheral neuropathy (Weintraub et al 2003), dysmenorrhea (Eccles 2005a, b), postoperative wound healing (Man et al 1999), knee osteoarthritis (Holcomb et al 1991;Hinman et al 2002;Harlow et al 2004;Wolsko et al 2004), and chronic pain syndromes including post-polio pain syndrome (Vallbona et al 1997), fibromyalgia (Colbert et al 1999;Alfano et al 2001), frozen shoulder (Kanai et al 2004;Kanai and Taniguchi 2006), pelvic pain (Brown et al 2002), and low back pain (Holcomb et al 1991;Kanai et al 1998). Four systematic literature reviews that assessed the overall effectiveness of SMF for pain relief came to contradictory conclusions (Wasiak 2001;Ratterman et al 2002;Eccles 2005a, b;Pittler et al 2007). Wasiak, basing his analysis on a single randomized controlled trial (RCT) of Collacott et al (2000) in which a possibly inadequate SMF dose was used, found ''no evidence for the effectiveness of therapeutic magnets in relieving pain''.…”
Section: Introductionmentioning
confidence: 97%
“…Wasiak, basing his analysis on a single randomized controlled trial (RCT) of Collacott et al (2000) in which a possibly inadequate SMF dose was used, found ''no evidence for the effectiveness of therapeutic magnets in relieving pain''. Ratterman's group reviewed seven RCTs and concluded that the scientific evidence to support the popular use of magnet therapy was lacking (Ratterman et al 2002). Eccles, on the other hand, in a 2005 review of 21 RCTs, stated that the weight of the evidence suggests that SMFs are able to induce analgesia.…”
Section: Introductionmentioning
confidence: 98%